The discovery of novel variants reveals the genetic diversity and potential origin of Seoul orthohantavirus. - Guopeng Kuang; Jing Wang; Yun Feng; Weichen Wu; Xi Han; Genyang Xin; Weihong Yang; Hong Pan; Lifen Yang; Juan Wang; Mang Shi; Zihou Gao (PLoS Neglected Tropical Diseases)
Seoul orthohantavirus (SEOV) has been identified as one of the main causative agents of hemorrhagic fever with renal syndrome (HFRS) in China. The virus was found circulating in rodent populations in almost all provinces of the country, reflecting the wide distribution of HFRS. Here, using the direct immunofluorescence assay (DFA) and real-time quantitative reverse transcription PCR (qRT-PCR) approach, we performed screening in 1784 small mammals belonging to 14 species of three orders captured in the main areas of HFRS endemicity in Yunnan province (southwestern China) and identified 37 SEOV-positive rats (36 Rattus norvegicus and 1 Rattus tanezumi). A 3-year surveillance of HFRS epidemics and dynamics of rodent reservoir density and virus prevalence implied a potential correlation between them. The subsequent meta-transcriptomic sequencing and phylogenetic analyses revealed three SEOV variants, among which two are completely novel. The ancestral character state reconstruction (ACSR) analysis based on both novel variants and documented strains from 5 continents demonstrated that SEOV appeared to originate near the southwestern area (Yunnan-Kweichow Plateau) of China, then could spread to other regions and countries by their rodent carriers, resulting in a global distribution today. In summary, these data furthered the understanding regards genetic diversity and the potential origin for SEOV. However, the expanding endemic foci in the province suggest that the virus is spreading over a wider region and is much more diverse than previous depicted, which means that increased sampling is necessary.